2023
DOI: 10.3390/biomedicines11030883
|View full text |Cite
|
Sign up to set email alerts
|

From NAFLD to MAFLD: Definition, Pathophysiological Basis and Cardiovascular Implications

Abstract: Non-alcoholic fatty liver disease (NAFLD) is defined as a chronic liver disease characterized by excessive fat accumulation in the liver without another obvious cause (no excessive alcohol consumption, hepatotoxic medications, toxins, viral infections, genetic hepatic diseases), therefore it is an exclusion diagnosis. The term NAFLD literally refers to non-alcohol related hepatopathy and does not adequately correlate with metabolic dysfunction and related cardiovascular risks. Therefore, researchers and scient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 104 publications
0
17
0
Order By: Relevance
“…Obesity, insulin resistance, and other metabolic diseases usually accompany MAFLD. [10,14,[52][53][54] Individually tailored behavioral interventions such as dietary changes and physical activity are among the main approaches used to treat patients with MAFLD. However, the expectations of tangible results by patients (e.g., quick weight loss) make lifestyle changes di cult to maintain in the long term.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity, insulin resistance, and other metabolic diseases usually accompany MAFLD. [10,14,[52][53][54] Individually tailored behavioral interventions such as dietary changes and physical activity are among the main approaches used to treat patients with MAFLD. However, the expectations of tangible results by patients (e.g., quick weight loss) make lifestyle changes di cult to maintain in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57][58] The high prevalence of MAFLD and other metabolic disorders, and the rapid increase in prevalence over the last decade calls for immediate action in addressing the onset and progression of the disease. [10,15,59] The association of the gut microbiota with different diseases, including MAFLD, opens the possibility for microbiome-related interventions as an alternative to classical approaches. However, despite major research efforts into the bacterial gut microbiota, examination of the impact and potential bene cial roles of the Bacteroidetes phylum is, surprisingly, lackluster, even more when considering the high presence of members of this phylum in the gut.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic dysfunction-associated fatty liver disease (MAFLD), previously known as non-alcoholic fatty liver disease (NAFLD), is a chronic liver disease characterized by excessive fat accumulation in the liver, without another obvious cause such as no excessive alcohol consumption, hepatotoxic medications, toxins, viral infections, genetic hepatic diseases [ 6 , 7 ]. MAFLD is defined as the accumulation of hepatic steatosis, as determined using imaging and/or liver biopsy and accompanied by at least one of three conditions, namely type 2 diabetes mellitus (T2DM), obesity, and metabolic dysregulation that can happen in both developed and developing countries [ 6 , 7 , 8 ]. The updated clinical guidelines from the American Association for the Research of Liver Diseases (AASLD), the American College of Gastroenterology, and the American Gastroenterological Association stipulate that the diagnosis of MAFLD should be based on three criteria: (1) evidence of increased hepatic fat on imaging, (2) absence of significant alcohol consumption (>30 g/day), and (3) absence of other known causes of chronic liver disease [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that even without direct signs of cell death, modi cations in the microbiota composition are associated with many diseases, such as irritable bowel syndrome (IBS), diabetes, cardiovascular disease and Metabolic dysfunction-associated fatty liver disease (MAFLD), previously known as Non-Alcoholic Fatty Liver Disease (NAFLD). [10][11][12][13][14][15] However, the bacterial gut microbiota is not the sole driver of disease. The oral microbiota has a major role in oral health, and recent evidence links its impact on systemic health and disease (recently reviewed by Baker et al, 2023).…”
Section: Introductionmentioning
confidence: 99%